Multi Loculated Hydrocephalus and Simple Hydrocephalus: Comparison of Outcomes in a Paediatric Population - Mukherjee, Sudipta Kumer; Rehman, Umar; Roy, Holly; Arman, DM; Hasnat, Md Aminul; Ziauddin, Md; Mahabub, AA; Rahman, Mohd Moshiur; Rahaman, Md Nafaur; Hoq, Md Ziaul; et al. (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Management for simple hydrocephalus in low/middle income countries include insertion of a ventriculoperitoneal shunt (VPS) or performance of an endoscopic third ventriculostomy (ETV). Objective: This present study was carried out to compare presenting features, surgical management and outcomes for patients with simple and loculated hydrocephalus. Methodology: This case-control study was performed in the Department of Paediatric Neurosurgery at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from July 2017 to June 2019. The patients with loculated hydrocephalus were included in the analysis and comparison made to case matched simple hydrocephalus controls. Presenting features, operative details, and outcomes measured by the Glasgow Outcome Scale- Paediatric (GOS) were recorded over a follow up period of one year. Results: A total number of 17 patients with loculated hydrocephalus were recruited for this study. Loculated patients underwent ETV (n=3), VPS (n=7), aqueductoplasty (n=1) and no procedure (n=6). Simple hydrocephalus patients underwent ETV (n=4), VPS (n=7), no procedure (n=2). Patients undergoing intraoperative irrigation had a mean GOS of 3 compared to a GOS of 6 in non-irrigated patients (p=0.0434). Mortality occurred in 9 patients (5 loculated HCP and 4 simple HCP). Mortality was seen to be higher in male patients (p<0.0001) and those with congenital aetiologies (p<0.0001). Conclusion: There is no statistically significant difference in mortality or GOS at follow up between the 2 groups. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):112-120